Clinical and epidemiological characteristics of the frequency and structure of edentulism in elderly and senile people of the Republic of Sakha (Yakutia) - N. I. Borisov; I. D. Ushnitsky (Эндодонтия Today, 2023)
Aim. Based on the results of the study of the frequency and structure of complete loss of teeth in the upper and lower jaws, to determine the need of elderly and senile people in prosthetics with complete removable orthopedic structures. Materials and methods. A dental examination was carried out in 5,791 people aged 60 to 93 years. At the same time, on the recommendation of WHO, a key age group of 65-74 years was formed. The study took into account the topography of the absence of teeth, gender, age, the presence and evaluation of previously manufactured complete removable dentures and the need for prosthetics. Results. A high prevalence of complete loss of teeth on the upper and lower jaws was found in the examined age groups of elderly and senile age. The largest proportion of complete loss of teeth of the upper and lower jaws was revealed in the age group of 75-84 years. At the same time, in elderly people, complete adentia is detected mainly in women, since men occupy a quarter of the gender ratio. Meanwhile, taking into account the indications for reprosthetics and the absence of prostheses with complete loss of teeth, the need for the manufacture of orthopedic structures in the form of complete removable prostheses in the surveyed population is determined. Conclusions. The obtained results dictate the need to improve orthopedic rehabilitation of patients with complete loss of teeth in the upper and lower jaws, taking into account the data obtained on the structure and frequency of complete loss of teeth in elderly and senile people.